2019
DOI: 10.3390/molecules24213917
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiplasmodial Activity of 1,2,3-Triazole-Naphthoquinone Conjugates

Abstract: A series of 34 1,2,3-triazole-naphthoquinone conjugates were synthesized via copper-catalyzed cycloaddition (CuAAC). They were evaluated for their in vitro antimalarial activity against chloroquine-sensitive strains of Plasmodium falciparum and against three different tumor cell lines (SKBr-3, MCF-7, HEL). The most active antimalarial compounds showed a low antiproliferative activity. Simplified analogues were also obtained and some structure–activity relationships were outlined. The best activity was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…The inhibition, however, did not correlate with the known carbonic anhydrase enzyme inhibition by primary sulfonamides [ 36 ]. SAR was established for 1,2,3-triazole-naphthoquinone analogues synthesized by a Cu(I)-catalyzed Huisgen 1,3-dipolar cycloaddition reaction against chloroquine-sensitive P. falciparum F-32 Tanzania [ 37 ]. It was found that the nature of substituents on the aromatic ring greatly influenced the antiprotozoal activity and further confirmed that the enzyme PfDHODH was the target of these compounds.…”
Section: Malaria As a Global Challengementioning
confidence: 99%
“…The inhibition, however, did not correlate with the known carbonic anhydrase enzyme inhibition by primary sulfonamides [ 36 ]. SAR was established for 1,2,3-triazole-naphthoquinone analogues synthesized by a Cu(I)-catalyzed Huisgen 1,3-dipolar cycloaddition reaction against chloroquine-sensitive P. falciparum F-32 Tanzania [ 37 ]. It was found that the nature of substituents on the aromatic ring greatly influenced the antiprotozoal activity and further confirmed that the enzyme PfDHODH was the target of these compounds.…”
Section: Malaria As a Global Challengementioning
confidence: 99%
“…Result revealed that the compound 57a exhibited the significant anti-HIV activity towards Coxsackie virus B4. SAR studies revealed that, the presence of the allyl group at N-4 of the 1,2,4-triazole ring and phenyl ring at terminal nitrogen of thioureas enhanced their activity [ 85 ]. …”
Section: Main Textmentioning
confidence: 99%
“…Guided by the concept of molecular hybridization, Oramas-Royo et al reported in 2019 [ 87 ], the synthesis and antiplasmodial activities of a series of 1,2,3-triazole-naphthoquinone conjugates ( Scheme 10 ). These compounds were synthesized through a copper(I) catalyzed Huisgen 1,3-dipolar cycloaddition [ 88 ] between O-propargylated naphthoquinone 70 and various alkyl or aryl azides with yields varying between 30% and 90%.…”
Section: Malaria Focused Mitochondrial Targetsmentioning
confidence: 99%
“…Nevertheless, they point out that further experimental assays and enzymatic kinetic studies are necessary to validate that para-furano-naphthoquinones could work as promising hits targeting Pf cyt bc1 and Pf DHODH. Guided by the concept of molecular hybridization, Oramas-Royo et al reported in 2019 [87], the synthesis and antiplasmodial activities of a series of 1,2,3-triazole-naphthoquinone conjugates (Scheme 10). These compounds were synthesized through a copper(I) catalyzed Huisgen 1,3-dipolar cycloaddition [88] between O-propargylated naphthoquinone 70 and various alkyl or aryl azides with yields varying between 30% and 90%.…”
Section: Bc1 And/or Dhodh Antimalarial Inhibitorsmentioning
confidence: 99%